Incitement, genocide, genocidal terror, and the upstream role of indoctrination: can epidemiologic models predict and prevent? - Elihu D. Richter; Dror Kris Markus; Casey Tait (Frontiers Media S.A., 2018)
Abstract We apply the models and tools of epidemiology and public health to propose a unified field theory showing the role of ideologies, indoctrination, and incitement, in genocide, genocidal terror, and terror by groups or individuals. We examine the effects of indoctrination and incitement as exposures and risks in relation to genocide and genocidal terror. Incitement has been recognized as a trigger to these outcomes but indoctrination is upstream to incitement. Population-wide exposure to indoctrination increases susceptibility to the effects of incitement. These relationships have been seen in all major genocides and genocidal terror in the late twentieth and twenty-first centuries. There is some insight into the relationship between ideology, incitement, and genocidal acts of violence from the so-called localized genocides in Bosnia, Rwanda, Darfur, Syria, and most recently, among the Rohingya in Myanmar. There is a need to recognize the upstream role of ideologies of hate in order to determine the degree to which indoctrination posed, and continues to pose, a contributing factor. Epidemiologic models, such as the iceberg model of exposure and disease and the concept of "sick individuals" and "sick populations," guide our understanding of the content and spread of indoctrination and incitement and can provide essential insights for prevention. The hateful indoctrination and ideologies behind genocidal violence must be countered and replaced by positive ideologies and role models that emphasize respect for life and human dignity for all.